IMPACT OF FUNDAMENTAL MACROECONOMIC FACTORS, COST EFFICIENCY, FIRMS POLICIES WITH SYSTEMATIC RISK AS MEDIATOR ON ISLAMIC FINTECH WELFARE PERFORMANCE : EVIDENCE FROM AN INDONESIA'S ISLAMIC FINTECH INSTITUTION - Dody Suhermawan; Mahjudin Mahjudin; Djoko Soelistya (PT. Mawadaku Sukses Solusindo, 2023)
This study tries to answer some questions on the impact of Fundamental Macroeconomic Factors, Cost Efficiency, Firms Policies to Islamic Fintech Walfare from economically emerging country like Indonesia. The analysis was conducted gradually by placing systematic risk and firm performance as intervening variables. This research, in specific, aims to test the gradual effect of macroeconomic fundamental factors on firm performance and firm value. The theoretical base applied to support this research was two established financial theories, such as agency and capital structure theory. This study used the samples of the Islamic Fintch Institution that listed in Indonesia's stock exchange, which the stocks actively traded in Indonesia's Stock Exchange. The data used was panel data, namely, the data of cross section and time series from the period of 2017 to 20019. The research results are; first, the macroeconomics variables (inflation, interest rate, exchange rate, and economic growth) have significant effect on systematic risks. On the other hand, systematic risks have significant effect on firm performance, and firm performance has significant effect on firm value. Second, the variables of firm policy (manager incentive and financial leverage) have significant effect on firm performance, and firm performance has significant effect on firm value. However, capital expenditure has insignificant effect on firm performance and firm value rather than manager incentive and financial leverage. Third, special findings from this research are that there is gradual process in influencing firm value so that firm performance has the role as intervening variable, which is the variables mediating the effects of macroeconomic variable (exchange rate), systematic risk, and firm policy (manager incentive) in Islamic financial technology welfare.